Digital evidence and its legitimacy in comparative systems - Ressa, Fatiha (The International tax journal, 2025)
The digital revolution has brought significant changes to criminal law, including the emergence of cybercrimes and the need to prove them using digital evidence. This evidence is characterised by its scientific and technical nature, its ease of replication, and its resistance to destruction. However, the validity of digital evidence depends on how it is collected and how persuasive it is to the judge. The extent of the judge’s discretionary authority varies according to the evidentiary system: the Latin system grants the judge considerable freedom, whereas the Anglo-Saxon system imposes strict criteria for the acceptance of digital evidence. The Algerian legislator has sought to adapt legislation to ensure the credibility and effectiveness of digital evidence in criminal proceedings.